Superconductivity in graphite-diamond hybrid. (March 2022) - Ge, Yanfeng; Luo, Kun; Liu, Yong; Yang, Guochun; Hu, Wentao; Li, Baozhong; Gao, Guoying; Zhou, Xiang-Feng; Xu, Bo; Zhao, Zhisheng; Tian, Yongjun
Abstract: Search for new high-temperature superconductors and insight into their superconducting mechanism are of fundamental importance in condensed matter physics. The discovery of near-room temperature superconductivity at more than a million atmospheres ushers in a new era for superconductors. However, the critical task of identifying materials with comparable superconductivity at near or ambient pressure remains. Carbon materials can always lead to intriguing surprises due to their structural diversity and electronic adjustability. Insulating diamond upon doping or external stimuli has achieved superconducting state. Thus, it still has a great opportunity to find superconducting ones with higher transition temperature ( T c ). Here, we report an intrinsic superconducting graphite-diamond hybrid through first-principles calculations, whose atomic-resolution structural characteristics have been experimentally determined recently. The predicted T c is approximated at 39 K at ambient pressure, and strain energizing can further boost T c to 42 K. The strong electron-phonon coupling associated with the out-of-plane vibration of carbon atoms at the junction plays a dominant role in the superconducting transition. Our work demonstrates the great potential of such carbon materials as high- T c superconductors, which will definitely attract extensive research. Graphical abstract: Gradia-CO, as one of the four classes of graphite-diamond hypothetical crystals, are predicted to be a kind of intrinsic superconducting carbon materials with high superconducting transition temperatures up to 39 K at ambient pressure, demonstrating the potential of carbon materials as high- T c superconductors. The superconductivity of this kind of hybrid carbon is mainly associated with electron-phonon coupling contributed by the out-of-plane vibration of carbon atoms at the junction between graphite and diamond units. Moreover, the superconducting transition temperature can be further elevated to above 40 K upon strain engineering. Image 1 Highlights: Predicting good superconductivity in graphite–diamond hybrid under ambient pressure. Strong electron-phonon coupling from the diamond–graphite junction. Opening a new avenue for the research of carbon-based superconductor.